Topography and structural diversity regulate ecosystem multifunctionality in a subtropical evergreen broad-leaved forest - Wang, Jiaming; Liu, Heming; Yang, Qingsong; Shen, Guochun; Zhu, Xuyang; Xu, Yue; Wang, Xihua (Frontiers in Forests and Global Change, 2023)
Forest functionality is generally considered a byproduct of forest diversity. Perhaps unsurprisingly, many researchers associate increasing multi-functionality with increasing diversity. Diversity, however, is an often-overused word that may describe a host of features, including the diversity of species, functional trait and structure. Furthermore, variable environmental features (such as topography) influence the interaction between forest plants and their function. Incorporating complex topography (like that associated with tropical and subtropical forests) into estimates of forest functionality is challenging and highly uncertain. In this paper, we applied structural equation models to disentangle the relative importance of topography and different components of what might be considered “plant diversity” to forest multifunctionality using repeated census of a 20-ha subtropical forest plot. We found that multifunctionality was principally influenced by structural diversity more so than either species composition or functional trait diversity. In our SEM model approach, we observed variations in topography could account for about 30% of variation in multifunctionality. Furthermore, variations in topography could indirectly influence forest multifunctionality by changing species composition, functional trait diversity, and structural diversity. Our work highlights the importance of topography and forest structure in regulating subtropical forest multifunctionality on the local scale. This suggests future subtropical forest management should focus on regulating forest structure. Namely, our results suggest land managers must take topography (and the complex interaction between topography and plant diversity) into account in order to build robust and multifunctional forests.